A review on the efficient hydrodeoxygenation of lignin-derived phenolic compounds over bimetallic catalysts - Guangming Liang; Xiaowen Bao; Yu Chen; Zhengtao Lin; Yao He; Riyang Shu (Fuel, 2027)

Melatonin inhibits ethylene biosynthesis by regulating MdERF1/MdERF3 pathway during apple fruit ripening - Chen Li; Qian Yu; Yanmin Du; Wenhui Wang; Yajing Si; Yuling Liang; Shijiao Lin; Guangxin Yang; Weiting Liu; Aide Wang; Yinglin Ji (Postharvest Biology and Technology, 2026)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Two-stage instance segmentation method based on Tunnel-SPVNet for shield tunnel segments - Yu Li; Huai-Na Wu; Dong-Lin Feng; Yu-Liang Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Multispectral nighttime light remote sensing: Data, applications, and challenges - Liang Zhong; Xinjian Wang; Zihao Zheng; Qiming Zheng; Shaoyang Liu; Yongpeng Lin; Zhanghao Chen; Yuanrong He; Peng Yang; Peng Yu; Zhiying Xie; Xiaosheng Liu (Remote Sensing of Environment, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Interface-engineered amorphous coatings for plasmon-enhanced charge separation in Ag/TiO2 photocatalysts - Tsung-Lin Yang; Yu-Kai Zhou; Pei-Kai Hsu; Chi-Liang Chen; Shih-Yun Chen (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages” [Food Res. Int. 217 (2025) 116764] - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Causal inference reveals the dominant role of climate-adaptation coupling in future potato production - Zhihao He; Tengcong Jiang; Lin Zhu; Ning Yao; Yi Li; Hao Feng; De Li Liu; Liang He; Jianqiang He; Qiang Yu (Agricultural Systems, 2026)

Corrigendum to “Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol” [Biores. Technol. 390 (2023) 129855] - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Assessing global flood-induced occurrence and transmission risks of biological contaminants - Ke Shi; Qian-Hang Huang; Yu-Xin Lin; Bin-Yuan Gao; Yu-Qi Wang; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Artificial intelligence-related technologies for municipal solid waste management: A review and new insights from smart cities - Tachin Chin; Ying Fan; Chien-Liang Lin; Yu-Cheng Lin; Kuo-Ti Liao (Sustainable Cities and Society, 2026)

Reducing carbon emission commitment constraints of Chinese passenger vehicle manufacturers through life cycle management - Keke Ji; Qing Yang; Zipeng Lin; Yuping Li; Xin Sun; Jiaxin Yu; Xingxing Liu; Liang Dong (Sustainable Production and Consumption, 2026)

Deciphering the effects of sulfonamide antibiotics on denitrification from a metagenomic perspective: inhibition of nitrite reduction and succession patterns of functional microorganisms - Qinmao Zhou; Yuyang Wang; Hebin Liang; Jin Huang; Jiayu Zhang; Ke Yu; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

The independent and joint effects of short-term exposure to ambient air pollutants on eczema in two cities of China - Tianjing Ouyang; Zhuoxuan Liang; Shujie Huang; Yingyin Liu; Ziqiang Lin; Qijiong Zhu; Weiquan Zeng; Yu Wang; Changchang Li; Jianxiong Hu; Guanhao He; Tao Liu; et al. (Journal of Hazardous Materials, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

A structure-constrained diffusion method for intelligent reinforcement design of bridge two-pile caps - Buyu Jia; Zhaofan Liang; Yujun Lin; Xiaolin Yu (Engineering Structures, 2026)

An injectable thiolated alginate/oxidized dextran hydrogel with curcumin-copper nanoparticles for corneal neovascularization after alkali burn - Zhongwu Bei; Lin Ye; Shiyu Liang; Qi Tong; Xicheng Li; Jianan Li; Xiaorui Yu; Yujia Wei; Xuyue Liang; Tingyu Yang; Yun Yang; Longqian Liu; et al. (Carbohydrate Polymers, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Toward clinically integrated computational pathology: advancing diagnostic insight and practice transformation - Bonan Chen; Xin Fang; Weiru Yu; Jialin Wu; Canbin Fang; Yuanke Liang; Jun Yu; Gary M.K. Tse; Ka Fai To; Haoyu Lin; Wei Kang (Science Bulletin, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

The Use of Double-tube Multiplex TaqMan Real-time RT-PCR for the Simultaneous Detection of Foodborne Viruses in Shellfish - Peng Lin; Ling Chen; Qiang Wan; Zhihe Cai; Liang Xue; Qinghua Ye; Fufeng Jiang; Xiaoying Qu; Jiahui Huang; Huishu Huang; Yu Ding; Moutong Chen; et al. (Food Control, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

Construction of conductive polyimide dressings for accelerated wound healing via an interfacial compatibility optimization and polyelectrolyte complexation synergistic strategy - Lizhi Lin; Kexiang Fan; Hang Luo; Jueying Yang; Huaping Liang; Yongqiang Feng; Lijie Li; Kelin Peng; Yu Chen (Chemical Engineering Journal, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Experimental investigation on the longitudinal bending and shear performance of shield tunnels based on Timoshenko beam theory - Zuxian Wang; Chenghua Shi; Linchong Huang; Yu Liang; Yuexiang Lin (Tunnelling and Underground Space Technology, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Dynamics and community succession of surface-associated biofilms on microplastics in a full-scale wastewater treatment plant - Yu Li; Dongqi Wang; Yanzhe Gong; Shengwei Zhang; Mengbo Huang; Wenqi Liang; Ruoyu Wu; Xiaosheng Jing; Yishan Lin (Journal of Water Process Engineering, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Aptamer-driven tetrahedral framework nucleic acids for targeted resveratrol delivery in ulcerative colitis therapy - Botao Liu; Siyi Yang; Jiale Liang; Lan Yao; Bo Huang; Yu Chen; Yun Wang; Yunfeng Lin (Chemical Engineering Journal, 2026)

Root-mediated oxygen transfer drives Methylobacter enrichment and secondary alcohol metabolism to strengthen chlorobenzene degradation in landfill rhizosphere systems - Liang-jie Li; Yu-fan Liu; Zhi-lin Xing; Kun Cao; Tian-tao Zhao (Biomass and Bioenergy, 2026)

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

Mitigating cloud effects in Sentinel-2 time-series image classification using PCA-enhanced imputation - Tee-Ann Teo; Yu-Liang Lin (International Journal of Remote Sensing, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A dual-responsive silica-based molecularly imprinted polymer for sustainable and specific adsorption of γ-aminobutyric acid from Moringa oleifera seeds - Jiabo Cheng; Jirui Sui; Xuanyi Yu; Kungang Li; Qi Liang; Chuancheng Lin; Mingxing Li; Chunying Li; Chunjian Zhao (Food Research International, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Purification, Identification, and Functional Validation of Anti-Inflammatory Peptides from Protein Hydrolysates of Asian Seabass, Lates Calcarifer by-Product - Hui-Chen Lin; Chung-Chih Tseng; Jia-Yu Lu; Hua-Yi Liang; Chun-Hung Liu (Marine Biotechnology, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

End-to-end intelligent rapid design method for bridge single-pile based on generative adversarial networks - Buyu Jia; Zhaofan Liang; Wentao Ou; Yujun Lin; Xiaolin Yu (Engineering Structures, 2026)

Feeding and fecundity of leaf beetle Monolepta hieroglyphica on different tissues of corn and three weed plants - Yu-Wei Wu; Lin-Hao Zheng; Jia-Liang Xu; Jing-Wen Wang; De-Wei Meng; Fei-Wu Li; Wen-Jing Xu (Arthropod-Plant Interactions, 2026)
The double-spotted leaf beetle (DLB), Monolepta hieroglyphica (Coleoptera: Chrysomelidae), is a polyphagous pest that causes considerable damage to corn in China. However, there is limited knowledge regarding the influence of host plants on the biology of this beetle. This study assessed the feeding of DLB on three corn tissues and three weed species, as well as the impact of host plants/tissues on DLB fecundity. The Feeding rate of DLB was significantly affected by interaction between host plants/tissues and sex, indicating sex-specific patterns of feeding choice. The feeding levels of DLB adults were affected only by host plants/tissues, following the order: common knotgrass > corn silk > corn leaf > Asian copperleaf > white goosefoot > corn kernel. The fecundity of single female adults fed on common knotgrass was the highest (44.70 ± 11.47 eggs), whereas that fed on corn leaf was the lowest (2.00 ± 0.88 eggs). These results underscore the significance of weeds as alternative DLB hosts in corn agroecosystems, improving our understanding of DLB biology and offering valuable insights for establishing and providing an integrated pest management (IPM) program.

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Correction: Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2026)

Integrated LC-Orbitrap-MS and network pharmacology decipher the pharmacological basis of Eucommiae folium in treating rheumatoid arthritis - Yasi Deng; Ling Liang; Haokai Lin; Xinyang Shen; Hao Zheng; Ying Deng; Xing Tian; Juan Huang; Ye Zhang; Bin Li; Huanghe Yu; Wei Wang (Molecular Diversity, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Impact of sulfonamides on microbial community and antibiotic resistome profiles in anaerobic digestion of swine wastewater - Qinmao Zhou; Hebin Liang; Jin Huang; Uli Klümper; Peiju Fang; Zehui Yu; Yuyang Wang; Thomas U. Berendonk; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Utilizing conjugation effect of nitrogen unshared electron to architect redox-active polymer for sodium-ion storage - Liang-Yu Wang; Shun-Yu Yao; Jing-Zhe Wan; Qi-Hang Wang; Chao Ma; Jiu-Lin Wang; Kai-Xue Wang (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Variations in hydrochemical characteristics and their controlling factors among different types of lakes in the northeastern region of the Qinghai-Xizang Plateau - Jiping Chen; Ling Li; Weijie Li; Bingbing Liang; Yu Lin; Yutai Dai; Mengdi Zhao; Hong Shen; Xi Yang; Qiang Gao; Xuwei Deng (Environmental Monitoring and Assessment, 2026)

Anchoring Mechanism of Tunnel Free Face Subjected to Dynamic–Static Combined Load - Yu Chen; Zinuo Deng; Linchong Huang; Hang Lin; Yixian Wang; Yu Liang; Cungang Lin (Rock Mechanics and Rock Engineering, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Solid phase iron-driven Feammox for continuous flow low carbon to nitrogen ratio wastewater: The dual role of functional bacteria recruitment and community coordination optimization - Chisheng Yu; Qiang Lin; Liang Zhu; Ancheng Luo; Xinyu Chen; Kaiying Chen; Tianyu Xu; Zhiwei Liang (Journal of Environmental Chemical Engineering, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Shifting drivers of lake ecology in northern Taiwan over the last 1800 years: From climate variability to human land-use change - Abdur Rahman; Yu-Xiong Chen; Jo-lin Lai; Ranjan Kumar Mohanty; Bushra Khatoon; Kaoru Kashima; Liang-Chi Wang (CATENA, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Atmospheric Submicron Aerosols Over the Tibetan Plateau: A Review - Lin Liang; Wenhui Zhao; Xiaomin Chen; Weiwei Hu; Pengfei Yu; Shan Huang (Current Pollution Reports, 2026)

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Avermectin and cyclobutrifluram cause oxidative stress and energy metabolic disorders of Caenorhabditis elegans - Jingyu Tian; Herui Zhang; Caihong Yu; Ronghua Lin; Liang Liu; Min Li; Yue Yin (Pesticide Biochemistry and Physiology, 2026)

Mechanisms of organic matter accumulation during Early Silurian carbon-cycle perturbations: Geochemical constraints from the inner shelf, Upper Yangtze, South China - Weizhen Chen; Jingchun Tian; Xiaobing Lin; Kailong Feng; Qingshao Liang; Wei Yu; Xing Wang; Shi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Modeling water quality in tidal reaches under data-scarce conditions: enhancing aquaculture carrying capacity in bays through upstream contamination control - Fangkun Lin; Zhipeng Luo; Zhiyu Zhang; Jun Chen; Wei Zhang; Lijun Liang; Ghada Eshaq; Xin Yu; Huabin Zeng (Journal of Hydrology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

An automated and intelligent monitoring system for shield tunneling muck evaluation integrating multimodal data - Zeyu Yue; Linchong Huang; Yuexiang Lin; Yu Liang; Mingfeng Lei; Jianjun Ma (Journal of Cleaner Production, 2026)

Effect of quorum sensing signal molecular analog 4-hydroxy-5-methyl-3(2H)-furanone on the microbial diversity and flavor characteristics of Sichuan Paocai - Chunhui Deng; Qin Peng; Xia Lin; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Lei Liu; Ziwei Liang; Yu Rao (International Journal of Food Microbiology, 2026)

Ecological presence and functional role of bacteriophages in fermented vegetables - Xia Lin; Chunhui Deng; Yue Shu; Shengshuai Li; Yunlong Song; Hong Kong; Ziwei Liang; Lei Liu; Yu Rao (Food Microbiology, 2026)

Dynamic response and damage mechanism of S-UHPC-S composite panels with various shear connectors subjected to contact detonation - Jun Yu; Yao Lu; Shi-Lin Liang; Li Chen; Guo-Kai Zhang (Engineering Structures, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Hyperbranched polyamine-graft-poly(ε-caprolactone) with integrated flame retardancy, plasticization, and filler-dispersion functions toward high-performance poly(vinyl chloride) plastics - Xing-Hao Wang; Liang Yang; Jing Zhao; Ze-Zhong Lin; Dan-Dan Shi; Yu Chen; Pei-Yao Chen (Chemical Engineering Journal, 2026)

Dual-zone electrostatic assisted filters: Quantifying corona charging vs. polarizing effects on bacterial disinfection across diverse species - Junzhou He; Mingrui Cao; Hongtao Xu; Qianshun Liang; Miao Yu; Saichong Zhang; Yufeng Su; Chaofan Lin; Zhijian Liu; Enze Tian (Building and Environment, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Magnetic mineral dissolution front delimited by late Holocene sediment accumulation acceleration in the inner shelf, northern South China Sea - Mingkun Li; Meng Tang; Liang Chen; Yongying Zeng; Rou Wen; Junyu Lin; Mingjie Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Outdoor-like running indoors: an enhanced adaptive treadmill with real-time physiological monitoring - Pei-Chun Hung; Yu-Chen Liu; Chun-Liang Lin; Wu-Chung Su; Chian-Yu Lu (Next Research, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2025)
Methylmercury (MeHg) is a potent neurotoxin and bioaccumulates in food webs. Microbial transformation of inorganic mercury (Hg) produces most of the MeHg in the marine environment. The gene pair hgcAB encodes for Hg methylation, a process predominantly attributed to anaerobic bacteria. However, recent studies indicate the formation of methylmercury in low-oxygen zones within marine water columns, although the mechanisms remain poorly understood. “Blue holes” are marine sinkholes containing redox gradients stratified with depth and high microbial diversity across a range of biogeochemical cycles. Here, we present the first metagenomic analysis focused on the potential for Hg methylation in a blue hole ecosystem. Yongle Blue Hole (YBH), currently the world’s deepest known blue hole, was selected as a representative site to investigate the genetic potential for Hg methylation and to explore the functional capabilities of putative Hg-methylators within this unique environment. Metagenomic analysis showed that the anoxic sulfidic deep water was likely to be a hotspot for Hg methylation, driven by abundant and diverse Deltaproteobacteria. In the suboxic intermediate layer, Nitrospina and Myxococcota dominated the Hg-methylating community. Furthermore, Hg methylators were found to have different lifestyles (free-living or particle-associated) and to occupy distinct ecological niches within the YBH. In addition, the contribution of sinking particles to Hg methylation, especially in the deep anoxic water column, was highlighted. Our study unveils the biodiversity and survival strategies of Hg methylators across distinct environments. The findings suggest that blue holes could serve as model stratified ecosystems for studying Hg methylation processes across different habitats.

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Dose-effect relationship and molecular mechanism of cellulose nanocrystals from green tea residue on the gel behavior of pea protein-derived amyloid fibrils - Jianxia Xu; Lu Lin; Xiyao Liang; Wenbin Zha; Wenzhe Yin; Yingnan Liu; Zhenyu Yu; Xiaonan Sui; Yaqing Xiao (Food Hydrocolloids, 2025)

IgY antibodies as a non-antibiotic approach to combat Vibrio vulnificus infection and gut microbiota dysbiosis in zebrafish - Duo Chen; Jingjing Yu; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2025)

Integrated analysis of lncRNA-miRNA-mRNA regulatory network revealing molecular mechanisms of immune response and ion transport in Eriocheir sinensis under alkalinity stress - Jun-Lei Ma; Yu-Lin Bai; Yi-Dong Liang; Ting Zhang; Lei You; Dong-Po Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Identification and semi-quantification of alkylated polycyclic aromatic hydrocarbons in PM2.5 filter samples using in-injection port thermal desorption coupled with two-dimensional gas chromatography and rapid-scanning quadrupole mass spectrometry (TD-GC×GC-qMS) - Manfei Lin; Yongming Feng; Xiao He; Bin-Yu Kuang; X.H. Hilda Huang; Yongmei Liang; Jian Zhen Yu (Atmospheric Pollution Research, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Preparation and characterization of IgY antibody and its application in immunochromatographic assay for bongkrekic acid and its isomer - Bin Wang; Xue-Ming Cao; Ting-Ting Yun; Xiao-Min Liang; Yi-Na Lu; Yu-Xin Zhong; Zhen-Lin Xu (Analytica Chimica Acta, 2025)

Mechanical performance analysis of a dual-spar floating wind farm considering different shared mooring systems - Xiang Lin; Jingrui Zhao; Wenzhou Liang; Zhishuai Liu; Zihang Yu (Frontiers in Marine Science, 2025)
Introduction In recent years, as floating wind turbines advance into deeper waters, mooring systems represent a growing share of the overall investment. Shared mooring can simplify mooring arrangements and improve the economic efficiency of wind farms. However, it also increases the dynamic complexity of multi-turbine systems, introducing risks of high tension levels and snap events under extreme conditions, which must be addressed during the mooring design phase. Methods This study compares the coupled dynamic responses of three typical shared mooring systems: pure steel cable, polyester rope with a clump weight, and chain with a buoy. Mooring design is based on the catenary equation, and time-domain simulations are conducted using OrcaFlex to analyze the impact of various shared mooring configurations on the hydrodynamics and mooring performance of wind turbine systems. Results The results show that, compared to the baseline configuration, the taut single-weighted configuration is more effective in reducing the fluctuation of mooring tension under extreme conditions, thus avoiding the occurrence of snap events. As the clump weight mass increases, the surge motion of the platform is effectively suppressed, but the heave and pitch motions may become more pronounced. Therefore, a balance must be struck between the clump weight mass, platform motion, and mooring tension to achieve optimal overall performance. The catenary with buoy configuration shows similar results to the taut single-weighted configuration; however, the maximum tension of shared mooring may occur at the buoy connection. Additionally, excessive net buoyancy can exacerbate the dynamic characteristics of the buoy and raise the risk of collision between the buoy and passing vessels. This study contributes to a deeper understanding of shared mooring systems and provides valuable guidance for their design.

Prediction on the seismic behaviour of a multi-stage anchored slope by a time-dependent displacement analysis - Yu-Liang Lin; Li Lu; Dan He; Xiaobin Chen; JunYi Duan (European Journal of Environmental and Civil Engineering, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Application of multi-dimensional isotope fractionation to characterize the biotic and abiotic transformation mechanisms of the herbicide 2,4-dichlorophenoxyacetic acid - Jukun Xiong; Yongyu Liang; Chang Yuan; Suyun Chen; Meicheng Wen; Wanjun Wang; Qinhao Lin; Yingxin Yu (Journal of Hazardous Materials, 2025)

Assessment for seawall modifications to mitigate land crabs roadkills from field experiments and agent-based modeling - Kuang-Yu Tseng; Yun-Ting Hsieh; Yu-Wen Chen; Ting-Yu Liang; Hui-Chen Lin (Journal of Environmental Management, 2025)

A novel esterase MfdS catalyzes ester bond cleavage and promotes the degradation of mefenpyr-diethyl by Hansschlegelia zhihuaiae S113 - Houyu Yu; Rongrong Zhang; Lin Lai; JingJing Liang; Thamer Y. Mutter; Xing Huang (Journal of Environmental Chemical Engineering, 2025)

A new exhalative sedimentary metallogenetic model for Permian manganese deposits in China - Zhichen Liu; Yu Liu; Sui Zhang; Lin Xiao; Jianxi Long; Deng Chen; Yang Wang; Zequan Wei; Yi Zheng; Liang Xiao (Journal of Asian Earth Sciences, 2025)

Co-adsorption of phosphate and rare earth elements (REEs) on goethite induce middle REE-enriched fractionation - Xiaoju Lin; Wenbin Yu; Xiaoliang Liang; Yoshio Takahashi; Jingwen Zhou; Yiping Yang; Meng Chen; Jianxi Zhu; Runliang Zhu; Hongping He (Geochimica et Cosmochimica Acta, 2025)

Multi-omics insights into flavor compounds production and constipation-relieving benefits of different Lactiplantibacillus plantarum-fermented cereal beverages - Wen-Jie Jiang; Ya-Xin Jiang; Lin Cheng; Yu-Chen Ning; Jia-Yi Hou; Fei-Liang Zhong; Ting Yuan; Xue-Gang Luo (Food Research International, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric isoprene across subtropical forests in Southern China - Haifeng Yu; Xiangcheng Wu; Lin Cheng; Wen Tan; Liang Zhu; Yunhua Chang (Atmospheric Environment, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Seven previously undescribed steroidal alkaloids from the fruit of Solanum nigrum L. and their biological activities - Liang-Yu Liu; Qing Peng; Yu-Ke Yang; Tong Wu; Li-Xian Chen; Li Lin (Phytochemistry, 2025)

Biodegradable Janus membrane for oil/water separation and unidirectional oil transport via electrospinning and plasma treatment - Hongshen Lin; Fangxia Yu; Jingxi Liang; Shenao Bai; Rongzong Cai; Pingfan Xu; Peikun Zhang; Yaofa Luo (Journal of Cleaner Production, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Radionuclides and heavy metals in surface sediments of the Bering and Chukchi Seas: distribution, source identification, and risk assessment - Jing Lin; Qiangqiang Zhong; Rong He; Fule Zhang; Hao Wang; Liang Wang; Dekun Huang; Tao Yu (Continental Shelf Research, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

Whitening and antioxidant activities of Inonotus sanghuang Extract and development of primary whitening gel products - Liang Zhang; Hui-Lin Zhao; Shang-De Peng; Sempere Deguol Mawunya; Yao Zhang; Hai-Chen Li; Yu Luo; Yan Wen (Natural Product Research, 2025)

Transforming waste into value: High-performance hollow fiber adsorbents from municipal solid waste incinerator bottom ash - Chiou-Liang Lin; Zi-Yu Chen; Zhen-Shu Liu (Waste Management, 2025)

Corrigendum to “FOXO3a reactivation mediates the synergistic cytotoxic effects of rapamycin and cisplatin in oral squamous cell carcinoma cells” [Toxicology and Applied Pharmacology 251 (2011) 8–15] - Liang Fang; Huiming Wang; Lin Zhou; Da Yu (Toxicology and Applied Pharmacology, 2025)

Desulfurization wastewater evaporation for zero liquid discharge: Water and chloride balance in coal-fired power plants - Heng Chen; Hang Yu; Dayang Liang; Ziyan Yu; Liliang Lin; Ning Zhao; Linjun Yang (Journal of Water Process Engineering, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Energy-saving low-frequency vibration-assisted riveting process for joining high-strength metallic structures with enhanced performance - Cong Shao; Jun Lin; Congxiao Yu; Yanjin Guan; Liang Chen; Xiangshan Kong; Cunsheng Zhang; Guoqun Zhao (Journal of Cleaner Production, 2025)

Influence of disaccharide and mixed starter cultures on the fermentation process in earthen jar of factory-produced Sichuan paocai - Qiu Zhong; Hua Xiong; Shengshuai Li; Kaiyu Guo; Yue Shu; Xia Lin; Yage Xing; Ziwei Liang; Xingchen Liu; Lei Liu; Yu Rao (Food Research International, 2025)

Insight into the enhancement mechanism of repeated freezing-thawing pretreatment promotes carboxymethylation for improving the properties of sweet potato starch: From a multiscale structural perspective - Li Niu; Siwen Yu; Xinyi He; Wei Liang; Qian Lin; Qi Zhao; Xinyu Wang; Ruijie Li; Wenhao Li (Food Chemistry, 2025)

Plasmonic nanoheater for formaldehyde degassing - Gaopan Chen; Peng Yu; Lian Yang; Roberto Caputo; Feng Lin; Liang Pan; Yang Gao; Hongxing Xu; Alexander Govorov; Zhiming Wang (Chemical Engineering Journal, 2025)

Path tracking control of paddy field weeder integrated with satellite and visual methods - Dongshun Chen; Qiaolong Wang; Yi Lin; Zenghong Ma; Liang Sun; Gaohong Yu (Computers and Electronics in Agriculture, 2025)

Mercury flows in a cement plant adopting circular economy policies - Liang Yu Chen; Chia Chi Hsu; Chin Lung Lin; Ming Lun Lu; Hung Lin Chiang; Moo Been Chang (Waste Management, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Investigation on shear strength of steel-concrete-steel composite beams with lacing bars - Shi-Lin Liang; Yan-Qing Yao; Jun Yu; Chee Kiong Soh; Long Yun (Engineering Structures, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Innovative immunosonogen nanoplatform combining sonodynamic oxygenation and immunomodulation for superior cancer therapy - Jiali Tang; Yanlu Chen; Hao Lai; Qi Zeng; Yu Li; Junqi Feng; Ningjing Lin; Ronghua Jin; Junjie Liu; Tao Luo; Zixuan Liang (Chemical Engineering Journal, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Assembly processes of rare and abundant microbial taxa are closely related to bacterial and fungal functionality during desert vegetation reestablishment - Zhouchang YU; Wei ZHANG; Pian DUO; Ying ZHANG; Xingfang TIAN; Lin SUN; Yuzheng GU; Junhong ZHANG; Jiaxing SONG; Ahejiang SAILIKE; Yujie LIANG; Rong FU; et al. (Pedosphere, 2025)

Redox-induced engineering of amorphous/crystalline MnFeOx catalyst enables H2O/SO2-tolerant NOx abatement at ultra-low temperatures - Liang-Yi Lin; Joy-In Huang; Hsin-Yu Tsai (Journal of Hazardous Materials, 2025)

Intelligently responsive PVDF MF membrane with improved antifouling and easy-cleaning performance for efficient separation of oil-water emulsion - Aida Aibulatova; Lin Yu; Zhen-Liang Xu; Jia-Rui Yang; Rui Jia; Yin-Xin Fang (Journal of Environmental Chemical Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Polyhalogenated heterocycle additive induced in-situ 3D gelatinous polymerization with polysulfides for shuttle effect inhibited lithium-sulfur batteries - Xingkai Ma; Xinmei Song; Yaoda Wang; Junchuan Liang; Tianyu Shen; Zuoao Wu; Lina Qin; Huan Li; Tianchen Yu; Huaizhu Wang; Zuoxiu Tie; Yichao Yan; et al. (Chemical Engineering Journal, 2025)

Regulation of reactive oxygen species in peroxymonosulfate activation by metal–organic framework-derived materials - Bolun Yu; Jun Chen; Aoli Tan; Shuoyang Li; Quanzhang Liu; Bowen Liang; Xiaohang Zhang; Zuhong Lin; Haipu Li; Jingjing Yao (Chemical Engineering Journal, 2025)

A multifunctional metformin loaded carboxymethyl chitosan/tannic acid/manganese composite hydrogel with promising capabilities for age-related bone defect repair - Jingle Chen; Chao Xie; Yucong Li; Qili Sun; Fengnian Yu; Kai Li; Haotian Gao; Zhaoquan Liang; Bin Tang; Lijun Lin (Carbohydrate Polymers, 2025)

An autocorrelation-based residual-stacking approach for GNSS multipath and diffraction mitigation and its application in high mountainous areas - Yumiao Tian; Wenhao Xiong; Yibing Liang; Yu Tang; Xi Mei; Xuefeng Yang; Miao Lin (Journal of Geodesy, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Experimental investigation of the heave behaviors of ballastless railways on expansive soil foundations - Junyi Duan; Shengji Liang; Yu Su; Yuliang Lin; Weiping Liu; Gang Wang; Li Lu (Transportation Geotechnics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Demonstration of a kW-scale flexible multi-fuel reforming power generation system for decentralized energy supply - Zaixing Wang; Yi Lin; Yu Guo; Fengli Liang; Zhenzong He; Jiajun Hu; Junkui Mao; Molly Meng-Jung Li (Chemical Engineering Journal, 2025)

Electrostatic-Induced Crystal-Rearrangement of Benzoquinones Cathode for Large-Scale All-Organic Aqueous Proton Batteries - Jianyong Zhang; Jingyuan Yu; Wenwei Zhang; Ahmed Eissa Abdelmaoula; Chunhua Han; Zhenzhen Dou; Feng Liang; Lin Xu (Chemical Engineering Journal, 2025)

Island-like FeS2@TiO2 heterojunction modified separator for enhanced polysulfide management in lithium-sulfur batteries - Jing Song; Luchao Yue; Yifan Dou; Kun Yang; Lixin Zhang; Lin Jiang; Hongrui Liang; Yu Cao; Tianwei Fan; Xujie Zhang; Guisheng Qi; Xuping Sun; et al. (Chemical Engineering Journal, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Transcriptional mechanisms underlying thiazolidine-4-carboxylic acid (T4C)-primed salt tolerance in Arabidopsis - Wei-Yung Hsu; Yi-Zhen Wu; Yu-Min Lin; Mei-Juan Zheng; Liang-Jwu Chen; Chuan-Ming Yeh (Plant Cell Reports, 2025)

Extraction, characterization, and biological activities of a novel polysaccharide extract from Fructus caryophylli - Qingtao Yu; Wenzhi Li; Jieyi Long; Ming Liang; Lingli Jiang; Xiaoliang Lin; Dongqing He; Zhuoyan Wu; Xiaole Xia (Journal of Natural Medicines, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

A breakthrough of immunoassay format for hapten: recent insights into noncompetitive immunoassays to detect small molecules - Yi-Fan Liang; Jin-Yi Yang; Yu-Dong Shen; Zhen-Lin Xu; Hong Wang (Critical Reviews in Food Science and Nutrition, 2025)

Estimation on the earthquake-induced displacement of an inhomogeneous and anisotropic anchored slope considering a time-dependent yield acceleration - Yu-liang Lin; Li Lu; Jun-yi Duan (Soil Dynamics and Earthquake Engineering, 2025)

Ecotoxicological effects of the neonicotinoid insecticide dinotefuran on springtails (Folsomia candida) at soil residual concentration - Jiale Zhang; Herui Zhang; Caihong Yu; Ronghua Lin; Yanhua Hou; Min Li; Huixin Liang; Liping Chen; Xinyue Gao; Siqi Chen (Pesticide Biochemistry and Physiology, 2025)

Evaluating European countries' progress towards SDGs: Insights from parallel SBM DEA analysis of economic, healthcare, environmental, and educational efficiencies - Tai-Yu Lin; Yung-Ho Chiu; Jia Sheng Lu; Liang-Chun Lu; Hsiu-Fang Chien (Journal of Environmental Management, 2025)

Waste to wealth: Waste liquid promotes rice growth in soda saline-alkali soil by improving Desulfocapsaceae abundance - Jianfeng Zhang; Xianfeng Lin; Xiaoyu Lin; Xu Song; Yu Wu; Fengyuan Jin; Hanchi Wang; Jing Liang; Jiejing Zhang (Journal of Environmental Chemical Engineering, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Spatiotemporal pattern of embodied carbon emissions from in-use steel stock in countries along the Belt and Road - Liang Zhong; Yongpeng Lin; Miao Yang; Yuanrong He; Xiaosheng Liu; Peng Yu; Zhiying Xie (Resources, Conservation and Recycling, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Complex cleavage of Ni(II)-EDTA in electroplating wastewater: Complex cleavage sites, degradation pathways and recovery of precipitates - Chengyang Nan; Qingjin Lin; Qiantong Liang; Tianyun Liang; Yu Huang; Zhijie Guan; Wencan Dai; Zhenhua Huang; Depeng Fan; Shuiyu Sun; Shoupeng Li (Journal of Water Process Engineering, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Dexlansoprazole is an aryl hydrocarbon receptor agonist - Kuo-Liang Wei; Shan-Chun Chen; Chih-Yi Lin; Yu-Ting Chou; Wei-Tin Kuo; Teik-Wei Chuah; Jyan-Gwo Joseph Su (Food and Chemical Toxicology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric decamethylcyclopentasiloxane (D5) in Eastern China - Haifeng Yu; Yunhua Chang; Lin Cheng; Wen Tan; Liang Zhu; Jianlin Hu (Atmospheric Environment, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Correction: CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial and temporal variation of nutrient distribution in the Yangtze River estuary and adjacent waters: Insights from GOCI data analysis - Chaozhi Yu; Cancan Lu; Yangdong Li; Hongli Li; Jun Lin; Liang Chang (Marine Environmental Research, 2025)

Rapid granulation of aerobic sludge for treatment of brewery wastewater: Aeration strategy and nitrogen removal mechanism - Songping Deng; Lidong Liu; Xiao-yan Li; Weiqi Xue; Jiajin Liang; Zehui Yu; Lin Lin (Journal of Environmental Chemical Engineering, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Efficient activation of sodium percarbonate by hydroxylamine-enhanced zero-valent transition metals for the removal of AZO: performance, free radical generation and mechanism - Qiantong Liang; Chengyang Nan; Xiangwu Huang; Qingjin Lin; Zhenyun Liang; Yu Huang; Peihong Zheng; Shoupeng Li; Shuiyu Sun (Chemical Engineering Journal, 2025)

Preparation of nanocellulose-silk fibroin stiff hydrogel and high absorbing-low expansion xerogel via polysaccharide-protein interactions - Yue Ma; Tian Huang; Zhixing Hu; Juan Yu; Liang Liu; Lin Lin; Meijuan Chen; Ruoxian Jia; Xin Li; Zhiguo Wang; Yimin Fan (Carbohydrate Polymers, 2025)

Sulforaphane acts through the NFE2L2/AMPK signaling pathway to protect boar spermatozoa from cryoinjury by activating antioxidant defenses - Guangzhi Zhang; Fei Wen; Yu Li; Pingyu Sun; Yang Li; Zhangtao Hu; Hui Wang; Yunhui Ma; Guodong Liang; Lin Chen; Ke Yang; Jianhong Hu (Theriogenology, 2024)

Shaking table experiment on seismic response of a three-stage slope supported by anchoring lattice beam - Yu-Liang Lin; Li Lu; Xiao-Bin Chen; Yuan Xue; Zhi-meng Wang (Soil Dynamics and Earthquake Engineering, 2024)

Functional characterization of four antenna-enriched odorant binding proteins in Rhaphuma horsfieldi reveals the importance of RhorOBP1 in odorant recognition and insecticide resistance - Yin-Lan Liang; Shun-Si Li; Ning-Na Yin; Shu-Lin Li; Yu-Yue Lu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Operando on-line monitoring of nanoplastics in real environmental water samples enabling an optical microfiber Mach-Zehnder interferometer - Hongtao Li; Aiyun Zheng; Hao Wu; Weisheng Wang; Xu Wang; Yangyang Yu; Lili Liang; Huojiao Sun; Jiping Lin; Liang Lu; Jialiang Lv; Hao Yuan; et al. (Journal of Environmental Chemical Engineering, 2024)

Mechanism and controlling factors of mass transport complexes migration: A case study of the mass transport complexes in the taranaki deep water basin, New Zealand - Yongsheng Zhou; Wei Wu; Jianwei Feng; Guangxu Wang; Aihua Fu; Shiqin Liang; Lulu Wu; Qingchao Li; Weiqing Liu; Zhendong Feng; Changsong Lin; Panpan Chen; et al. (Geomorphology, 2024)

Structural behavior of S-UHPC-S composite wall strips with waved tie bars: Experiment, simulation, and design - Shi-Lin Liang; Jun Yu (Engineering Structures, 2024)

High-performance COFs composite nanofiltration membrane fabricated by organobase catalyst - Lin Yu; Jia-Yue Dai; Zhen-Liang Xu; Yin-Xin Fang; Rui Jia; Yong-Jian Tang (Desalination, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Rhizosphere Effect Enhanced the Immobilization Efficiency of Mercapto-Palygorskite for Cd in Alkaline Soil: Mechanism from the Perspective of Microorganism - Yu Zhang; Yingming Xu; Xuefeng Liang; Yuebing Sun; Lin Wang (Journal of Soil Science and Plant Nutrition, 2024)

Novel Pathogenic Mutation of P209L in TRPC6 Gene Causes Adult Focal Segmental Glomerulosclerosis - Tianxi Yu; Yongqiang Ji; Xin Cui; Ning Liang; Shuang Wu; Chongjun Xiang; Yue Li; Huiying Tao; Yaqi Xie; Hongwei Zuo; Wenting Wang; Nauman Khan; et al. (Biochemical Genetics, 2024)

Transcriptome analysis of hepatopancreas revealed the role of autophagy under nitrite stress in Pacific white shrimp (Penaeus vannamei) - Xinghao Lin; Zhengxinyu Liu; Jiaqian Chen; Xiaotong Huang; Wanghao Du; Yu Zhang; Beibei Dong; Qingjian Liang (Aquaculture International, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Chronic dietary exposure to glyphosate-induced connexin 43 autophagic degradation contributes to blood-testis barrier disruption in roosters - Qing Liang; Bao-You Liu; Tian-Lin Zhang; Hai-Jing Zhang; Yu-Long Ren; Hai-Peng Wang; Hao Wang; Lin Wang (Science of The Total Environment, 2024)

Investigation of factors affecting oil-water separation efficiency in micro-bubble micro-cyclonic flow air flotation - Wei Wang; Xiang Zhao; Xu Bai; Xue-liang Ma; Wei Lin; Jiu-yang Yu (Journal of Water Process Engineering, 2024)

Unveiling the pathogenic and multidrug-resistant profiles of Vibrio alfacsensis: A potential identified threat in turbot (Scophthalmus maximus) aquaculture - Ren-Ge Hu; Lei Yang; Li-Yan Wang; Yu-Lin Yang; Hong-Jin Li; Bin-Tong Yang; Yuan-Huan Kang; Zhen-Lin Liang; Wei Cong (Journal of Hazardous Materials, 2024)

Interfacial polymerization modulated by COFs interlayer to fabricate efficient mono/divalent ions separation nanofiltration membrane - Yin-Xin Fang; Yu-Fei Lin; Zhen-Liang Xu; Dibakar Pandaya; Sun-Jie Xu (Desalination, 2024)

Differential response of soil bacteria and fungi to carbon and respiration components in abandoned grasslands on the Loess Plateau, China - Xingfang Tian; Ying Zhang; Yujie Liang; Rong Fu; Lin Sun; Zhouchang Yu; Jiayi Shi; Ahejiang Sailike; Hongjian Hao; Wei Zhang (Plant and Soil, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Photoreduction of carbon dioxide into methane and ethylene using TiO2 inverse opal-derived PCN-222(M) - Fang-yu Liang; Yen-Ping Peng; Kun-Yi Andrew Lin; Po-Jung Huang (Journal of Environmental Chemical Engineering, 2024)

Effects of the Lactobacillus fermentation on Dendrobium officinale polysaccharide: Structural, physicochemical properties and in vitro bioactivities - Huasi Lin; Yanan Cheng; Lanxi Liang; Xiaoting Qin; Xuewen Dong; Yue Guo; Qiang Yu; Guowen Zhang; Xiaobo Hu (Food Bioscience, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Regulating iron center by defective MoS2 for superior Fenton-like catalysis in water purification: The key role of surface interaction and superoxide radical in accelerating metal redox-cycling - Ai-Yong Zhang; Zhi-Xian Lin; Jing-Yu Zhang; Ming-He Zhang; Chi Zhang; Lu Zhao; Liang Liu; Wei Da; Lyumeng Ye (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Carbon dots with tunable excitation-independent fluorescence and organelle-specific targeting via core graphitization and surface groups engineering - Ming-Yuan Sun; Bao-Hua Tian; Xin-Xin Li; Yu Li; Yu Lei; Xi-Lin Guo; Qiang Miao; Hao Li; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Vertical 3D printing of rGO/CNTs arrays for thermal interface materials with in-situ local temperature monitoring function - Ruidi Xia; Shuaikang Zhu; Fangzheng Zhen; Yu Du; Jianwei Zhang; He Yang; Miao Wu; Bo Zhao; Zhenyi Qi; Minsu Liu; Lin Jiang; Zhiqiang Liang (Chemical Engineering Journal, 2024)

Three-dimensional mixed-valence polyoxovanadates@polyaniline architecture towards high-performance rechargeable aqueous zinc-ion batteries cathode - Xue-Wei Liang; Yu-Ying Yang; Wen-Fei Di; Si-Yu Chen; Rui Zhang; Jisong Hu; Dunmin Lin; Yu Huo (Chemical Engineering Journal, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

High-molecular-weight dissolved organic matter enhanced phosphorus availability in paddy soils: Evidence from field and microcosm experiments - Hai-Bo Wang; Xi-Peng Liu; Bing-Jie Jin; Yu-Chen Shu; Cheng-Liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Soil and Tillage Research, 2024)

Tailoring component incorporation for homogenized perovskite solar cells - Wenhan Yang; Junmin Xia; Yuexin Lin; Hao Gu; Fengqiang Ma; Yumin Ren; Fenqi Du; Dejian Yu; Jinfeng Liao; Yiwang Chen; Guojia Fang; Shengchun Yang; et al. (Science Bulletin, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Enhanced adsorption of trace carbon dioxide from acetylene using Polyethyleneimine-Diethanolamine blends - Jiajin Huang; Yongsheng Huang; Danxia Lin; Liang Yu; Guang Miao; Mengxuan Cao; Xingbei Wu; Hao Wang; Qibin Xia (Chemical Engineering Journal, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Synergistic modulation of hydrogen bond network reconstruction and pH buffering of electrolyte enables highly reversible Zn anode - Xincheng Liang; Xingfa Chen; Zhixiang Zhai; Tianqi Yu; Huyi Yu; Haiquan Wang; Dexin Meng; Lin Peng; Shibin Yin (Chemical Engineering Journal, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Research on the rapid tissue breeding technology of the endangered plant Cibotium barometz (L.) J. Sm. - Qiaoling Yu; Wei Lin; Xingjian Yu; Ben Qin; Ying Liang; Fan Wei; Shuangshuang Qin; Kunhua Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2024)
Aging is a natural process associated with chronic inflammation in the development of vascular dysfunction. We hypothesized that chemokine C-C motif ligands 4 (CCL4) might play a vital role in aging-related vascular dysfunction. Circulating CCL4 was up-regulated in elderly subjects and in aged animals. CCL4 inhibition reduced generation of reactive oxygen species (ROS), attenuated inflammation, and restored cell functions in endothelial progenitor cells from elderly subjects and in aged human aortic endothelial cells. CCL4 promoted cell aging, with impaired cell functioning, by activating ROS production and inflammation. CCL4 knockout mice and therapeutic administration of anti-CCL4 neutralizing antibodies exhibited vascular and dermal anti-aging effects, with improved wound healing, via the down-regulation of inflammatory proteins and the activation of angiogenic proteins. Altogether, our findings suggested that CCL4 may contribute to aging-related vascular dysfunction via activating oxidative stress and endothelial inflammation. CCL4 may be a potential therapeutic target for vascular protections during aging.

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Spatial distribution and assembly processes of bacterial communities in riverine and coastal ecosystems of a rapidly urbanizing megacity in China - Hebin Liang; Jin Huang; Yu Xia; Ying Yang; Yang Yu; Kai Zhou; Lin Lin; Xiaoyan Li; Bing Li (Science of The Total Environment, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Insights into the role of endogenous humic acid on antibiotics bioadsorption process in wastewater: Mechanisms and potential implications - Lin Qiang; Luo Ancheng; Yu Chisheng; Chen Kaiying; Yasir Hamid; Liang Zhiwei; Wang Yunlong; Yang Wenchen (Journal of Water Process Engineering, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

The bioaugmentation effect of microbial inoculants on humic acid formation during co-composting of bagasse and cow manure - Mengling Lu; Yuhao Hao; Binfeng Lin; Zhi Huang; Yu Zhang; Liang Chen; Kai Li; Jianbin Li (Environmental Research, 2024)

A single-electrode evaluation method used for analyzing the working mechanism and capability of integrated membrane capacitive deionization - Qinghao Wu; Qifeng Wang; Chen Yu; Shanfu Lu; Kun Lin; Yan Xiang; Kuichang Zuo; Doron Aurbach; Dawei Liang (Desalination, 2024)

Immune-enhancing activity of compound polysaccharide on the inactivated influenza vaccine - Yang Zhang; Depeng Wang; Daotong Tan; Anqi Zou; Zhe Wang; Hao Gong; Yu Yang; Lishan Sun; Xiaoliang Lin; Ming Liang; Yi Yu; Xiaoxi He; et al. (Carbohydrate Polymers, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Inflammation-Responsive Mesoporous Silica Nanoparticles with Synergistic Anti-inflammatory and Joint Protection Effects for Rheumatoid Arthritis Treatment - Ye-zhen Wu; Wen-yu Chen; Ying Zeng; Qi-lin Ji; Yue Yang; Xu-liang Guo; Xiu Wang (Pharmaceutical Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Occurrence of micropollutants in rural domestic wastewater in Zhejiang Province, China and corresponding wastewater-based epidemiology analysis - Lin Qiang; Yu Chisheng; Chen Kaiyin; Yasir Hamid; Luo Ancheng; Liang Zhiwei; Xu Tianyu (Science of The Total Environment, 2024)

Thiol-functionalized black carbon as effective and economical materials for Cr(VI) removal: Simultaneous sorption and reduction - Kamonchanok Huangmee; Liang-Ching Hsu; Yu-Min Tzou; Yen-Lin Cho; Chih-Hao Liao; Heng Yi Teah; Yu-Ting Liu (Journal of Environmental Management, 2024)

Identification and function analysis of BCL2 in immune response of Pteria penguin - Wenhao He; Jinji Lin; Feifei Yu; Yang Leng; Zhenni Pan; Qiwen Liang; Siying Liu; Xinyue Huang (Fish & Shellfish Immunology, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

Taxonomy of Two New Peritrich Ciliates (Protozoa: Ciliophora) from Inland Saltwaters of China - Ying Yu; Yong Zhang; Ziyao Liang; Jiqiu Li; Xiaofeng Lin (Journal of Ocean University of China, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Rh/InGaN1−O nanoarchitecture for light-driven methane reforming with carbon dioxide toward syngas - Yixin Li; Jinglin Li; Tianqi Yu; Liang Qiu; Syed M. Najib Hasan; Lin Yao; Hu Pan; Shamsul Arafin; Sharif Md. Sadaf; Lei Zhu; Baowen Zhou (Science Bulletin, 2024)

Comparative analysis of chlorine-resistant bacteria after chlorination and chloramination in drinking water treatment plants - Yijun Wei; Haiyan Wu; Xudong Zhang; Yongbing Liang; Danyang Shi; Lin Wang; Haibei Li; Hongling Yu; Dong Yang; Shuqing Zhou; Tianjiao Chen; Zhongwei Yang; et al. (Journal of Hazardous Materials, 2024)

Self-assembled C-Ag hybrid nanoparticle on nanoporous GaN enabled ultra-high enhancement factor SERS sensor for sensitive thiram detection - Hongpeng Zhou; Jiaoyan Qiu; Yunhong Zhang; Yanbo Liang; Lin Han; Yu Zhang (Journal of Hazardous Materials, 2024)

Optical investigation on effects of diesel injection strategy on ammonia/diesel dual fuel combustion characteristics and flame development - Wenpeng Zeng; Wanchen Sun; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Melatonin alleviates glyphosate-induced testosterone synthesis inhibition via targeting mitochondrial function in roosters - Yu-Long Ren; Qing Liang; Cai-Yu Lian; Wei Zhang; Lin Wang (Environmental Pollution, 2024)

Exploring a sustainable binder for capacitive deionization technology to achieve high salt and zinc ion removal efficiency - Bin Xie; Neng Yan; Yu Liang; Jing Li; Lin Zhang; Junjie He (Desalination, 2024)

Multi-functional hydrogen- and oxygen-capturing FeCo-N-C catalyst with improved hydrogenation of nitroarenes and ORR activity - Hsiu-Chung Tu; Yu-Lin Hsiao; Yi-Dong Lin; Yan-Gu Lin; Ding-Liang Liao; Ko-Shan Ho (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Minimal learning parameters-based simplified robust adaptive saturated control for dynamic positioning ship with input magnitude and rate saturations - Kun Liang; Jiawei Cui; Peng Lu; Yu Chen; Xiaogong Lin; Yaowei Sun; Qiang Zhang; Xinling Wen; Ying Duan (Ocean Engineering, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

In vitro digestion and fecal fermentation of selenocompounds: impact on gut microbiota, antioxidant activity, and short-chain fatty acids - Shuojia Liang; Junlei Yu; Meng Zhao; Sha Chen; Xiang Lu; Fayin Ye; Jia Chen; Guohua Zhao; Lin Lei (Food Research International, 2024)

Corrigendum to “Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections” Eng Struct 302 (2024) 117405 - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

Effects of interface conditions on tribological and hysteretic behaviors of symmetric friction connections - Hongliang Liu; Liang-Jiu Jia; Yu-Ao Lin; Ping Xiang (Engineering Structures, 2024)

Unraveling metabolic fate of a veterinary antibiotic thiamphenicol via the multi-omic approach - Jiayu Zhang; Fangliang Guo; Hebin Liang; Ke Yu; Wan Cai; Lin Lin; Xiaoyan Li; Bing Li (Chemical Engineering Journal, 2024)

Highly active and stable VOx/TiO2 nanosheets for low-temperature NH3-SCR of NO: Structure-directing role of support - Liang-Yi Lin; Yu-Chen Wang; Zi-Lan Liu (Chemical Engineering Journal, 2024)

Directly capturing native fatty acid synthase from cancer cells by affinity-based probe for precise inhibitor discovery - Yuanyuan Lin; Huaqiu Lu; Jinhao Yu; Xuan Chen; Ningbo Chen; Huamin Zhang; Lu Ye; Yimin Chen; Weiyang Tang; Guizhong Xin; Jian-Liang Zhou (Chemical Engineering Journal, 2024)

Effect of phosphate on the sorption and fractionation of rare earth ions on kaolinite surface and its geochemical significance - Jingwen Zhou; Xiaoliang Liang; Wenbin Yu; Xiaoju Lin; Puqiu Wu; Yanhong Jiang; Deyin Huang (Chemical Geology, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Rapid identification and characterization of pineapple fruitlet core rot pathogens on the ‘TN20’ cultivar in Taiwan - Yu-Ping Liang; Kuan-Yu Lin; Su-Yu Lai; Hui-Fang Ni (European Journal of Plant Pathology, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Large-n quasi-phase-pure two-dimensional halide perovskite: A toolbox from materials to devices - Zijia Li; Yuexin Lin; Hao Gu; Nan Zhang; Bin Wang; Hairui Cai; Jinfeng Liao; Dejian Yu; Yiwang Chen; Guojia Fang; Chao Liang; Shengchun Yang; et al. (Science Bulletin, 2024)

Transcriptome and ultrastructural analysis revealed the mechanism of Mercapto-palygorskite on reducing Cd content in wheat - Yu Zhang; Yingming Xu; Qingqing Huang; Xuefeng Liang; Yuebing Sun; Lin Wang (Journal of Hazardous Materials, 2024)

The underappreciated role of fugitive VOCs in ozone formation and health risk assessment emitted from seven typical industries in China - Zhiling Liang; Yunjiang Yu; Bingbing Sun; Qian Yao; Xihua Lin; Yongsheng Wang; Jianping Zhang; Yingzi Li; Xuefeng Wang; Zhengzheng Tang; Shexia Ma (Journal of Environmental Sciences, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

BDE-47 induces metabolic dysfunction-associated steatotic liver disease (MASLD) through CD36-mediated increased fatty acid uptake and PPARα-induced abnormal fatty acid oxidation in BALB/c mice - Beibei Xia; Rongfei Yu; Junxiong Liu; Dongmeng Liu; Shasha Li; Liu Yang; Nan Liu; Bosen Liang; Jiajing Zeng; Jinhua Wei; Guimiao Lin (Toxicology Letters, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Corrigendum to “Establishing a weighted methodology for human health risk assessment of cadmium based on its equilibrium speciation in groundwater” [J. Clean. Prod. 322 (2021) 129053] - Fangfang Miao; Yimei Zhang; Yu Li; Xi Liang; Qianguo Lin; Yinzhuang Zhou (Journal of Cleaner Production, 2024)

Mineralogy and geochemistry of magnetite in the Zhdanov Ni-Cu-(PGE) deposit in the Pechenga ore field, Russia: Implications for the formation of magmatic sulfide ores - Qing-Lin Liang; Xie-Yan Song; Valery Smolkin; Nadezhda A. Krivolutskaya; Song-Yue Yu; Lie-Meng Chen (Journal of Asian Earth Sciences, 2024)

Optical diagnostic study of internal and external EGR combined with oxygenated fuels of n-butanol, PODE3 and DMC to optimize the combustion process of FT synthetic diesel - Wanchen Sun; Genan Zhu; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Wenpeng Zeng; Xin Zhang; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Polyamide infiltration phenomenon on microfiltration support reduced by covalent organic frameworks net for faster desalination - Yin-Xin Fang; Yu-Fei Lin; Zhen-Liang Xu; Jia-Yue Dai; Dibakar Pandaya (Desalination, 2023)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Greenwater due to plunging breaking wave impingement on a deck structure. Part 1: Experimental investigation on fluid kinematics - Wei-Liang Chuang; Ting-Chieh Lin; Yu-Jan Wang (Ocean Engineering, 2023)

Evaluation of species thermal sensitivity with individual-based physiological performance - Liang Zhang; Yu-Yang Zhang; Lin-Xuan Ma; Yun-Wei Dong (Marine Environmental Research, 2023)

Predicting carbon futures prices based on a new hybrid machine learning: Comparative study of carbon prices in different periods - Xi Zhang; Kailing Yang; Qin Lu; Jingyu Wu; Liang Yu; Yu Lin (Journal of Environmental Management, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Heterogeneous photocatalysis coupled with Fenton-Like reaction for fluoroquinolone antibiotics degradation by poly (Triazine Imide): From mechanism to application in a continuous flow catalytic system - Jingjun Qin; Zhang Liu; Weicheng Xu; Ximiao Zhu; Fawen Liang; Yutang Yu; Yuanzhi Zheng; Lang Yao; Honghua Zhang; Kaichun Lin; Jianzhang Fang; Zhanqiang Fang (Chemical Engineering Journal, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Study on the shear mechanics of gas hydrate-bearing sand-well interface with different roughness and dissociation - Jianwei Li; Yu Zhang; Liang Lin; You Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Oxygen doped graphite carbon nitride as efficient metal-free catalyst for peroxymonosulfate activation: Performance, mechanism and theoretical calculation - Shaofeng Xiang; Yu Lin; Tongda Chang; Bingrui Mei; Yuhang Liang; Ziqian Wang; Wenwu Sun; Chun Cai (Chemosphere, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Boron nitride aerogels incorporated with metal nanoparticles: Multifunctional platforms for iodine capture and detection - Gen Li; Jianli Liang; Jing Lin; Hongyu Li; Yan Liu; Guoyang Xu; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Simplified synthesis of direct Z-scheme Bi2WO6/PhC2Cu heterojunction that shows enhanced photocatalytic degradation of 2,4,6-TCP: Kinetic study and mechanistic insights - Jinfan Zhang; Zili Lin; Zongshun Yu; Yudan Zhang; Danluo Liang; Yingyi Chen; Yu Chen; Ping Chen; Haijin Liu; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

An optical study of the combustion and flame development of ammonia-diesel dual-fuel engine based on flame chemiluminescence - Wanchen Sun; Wenpeng Zeng; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu; Fei Wu (Fuel, 2023)

A modified Newmark block method for determining the seismic displacement of a slope reinforced by prestressed anchors - Li Lu; Yu-Liang Lin; Dong-Dong Guo; Hao Xing; Zhen Zhang; Jun-Yi Duan (Computers and Geotechnics, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Impact of the winter Arctic sea ice anomaly on the following summer tropical cyclone genesis frequency over the western North Pacific - Shangfeng Chen; Wen Chen; Bin Yu; Liang Wu; Lin Chen; Zhibo Li; Hasi Aru; Jingliang Huangfu (Climate Dynamics, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Genome-wide transcriptomics and microRNAomics analyses uncover multi-faceted mechanisms to cope with copper stress in ancient macrobenthos amphioxus - Lin-Yu Yang; Qian-Hua Zhu; Jun-Yuan Chen; Lian-Bing Lin; Ming-Zhong Liang; Qi-Lin Zhang (Journal of Hazardous Materials, 2023)

Fermentation of grapefruit peel by an efficient cellulose-degrading strain, (Penicillium YZ-1): Modification, structure and functional properties of soluble dietary fiber - Wenjie Ma; Yuting Liang; Huasi Lin; Yi Chen; Jianhua Xie; Fengling Ai; Ziwen Yan; Xiaobo Hu; Qiang Yu (Food Chemistry, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

Combination of surfactants and enzyme cocktails for enhancing woody biomass saccharification and bioethanol production from lab-scale to pilot-scale - Wei Qi; Qifa Feng; Wen Wang; Yu Zhang; Yunzi Hu; Usama Shakeel; Lin Xiao; Lan Wang; Hongzhang Chen; Cuiyi Liang (Bioresource Technology, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Numerical and experimental analysis of LBE flow and heat transfer characteristics in hexagonal rod bundles - Xingguang Zhou; Dalin Zhang; Jie Liu; Chao Lin; Yu Liang; Wenxi Tian; Suizheng Qiu; Guanghui Su (Annals of Nuclear Energy, 2023)

Perceptions of Taiwanese owners and behaviour veterinarians on behavioural problems in dogs and preferred training approaches - Hao-Yu Shih; Yu-Min Chang; Kris Descovich; Wen-You Liang; Chung-Hsi Chou; Yi-Chun Lin (Applied Animal Behaviour Science, 2023)

Distribution and potential health risks of perfluoroalkyl substances (PFASs) in water, sediment, and fish in Dongjiang River Basin, Southern China - Wang Xu; Shibo Li; Weimin Wang; Ping Sun; Chunyang Yin; Xuxia Li; Liang Yu; Gang Ren; Lin Peng; Fei Wang (Environmental Science and Pollution Research, 2023)

Ionomic analysis reveals the mechanism of mercaptosilane-modified palygorskite on reducing Cd transport from soil to wheat - Yu Zhang; Yingming Xu; Xuefeng Liang; Lin Wang; Yuebing Sun; Qingqing Huang; Xu Qin (Environmental Science and Pollution Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Magnetic Z-scheme CuFe2O4/MIL-101(Fe) toward chlorpyrifos degradation: Photocatalytic mechanism, degradation pathways, and intermediates toxicity evaluation - Yu Tian; Qian Liu; Shanshan Lin; Xiaoxia Liang; Sara Khan; Xia Yang; Xianze Wang (Journal of Environmental Chemical Engineering, 2023)

New insights into differential salinity tolerance between autotrophic and heterotrophic partial nitrification - Lin Qiang; Wang Yunlong; Yu Chisheng; Luo Ancheng; Liang Zhiwei (Journal of Environmental Chemical Engineering, 2023)

Research on hydrate-bearing reservoir deformation and wellbore wall stability during natural gas hydrate exploitation - Jianwei Li; Yu Zhang; Shengjie Di; Liang Lin; You Zhou (Geomechanics for Energy and the Environment, 2023)

Preparation of Single-Ni atom active points by anchoring Anderson polyoxometalate in HKUST-1 for efficient Symmetric/ Asymmetric device energy storage and electrocatalytic overall water splitting - Yu Liang; Hongquan Jiang; Hong Lin; Chunmei Wang; Kai Yu; Chunxiao Wang; Jinghua Lv; Baibin Zhou (Chemical Engineering Journal, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Genetic variants of SOS2, MAP2K1 and RASGRF2 in the RAS pathway genes predict survival of HBV-related hepatocellular carcinoma patients - Qiuling Lin; Moqin Qiu; Xueyan Wei; Zhouyun xiang; Zihan Zhou; Iiangyan Ji; Xiumei Liang; Xianguo Zhou; Qiuping Wen; Yingchun Liu; Hongping Yu (Archives of Toxicology, 2023)

Transcriptome analysis reveals the feeding response and oxidative stress in juvenile Micropterus salmoides fed a low-fish-meal diet with enzyme-hydrolysed intestinal mucosa protein substitution - Heng Yu; Xianping Ge; Lin Zhang; Xiaoru Chen; Mingchun Ren; Hualiang Liang (Aquaculture, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Silicon isotopic compositions of altered Oceanic crust samples from IODP U1365 and U1368: Effect of low-temperature seawater alteration - Hui-Min Yu; Lin Yang; Guo-Liang Zhang; Fang Huang (Chemical Geology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Dietary chitosan alleviates intestinal and liver injury of hybrid sturgeon (Acipenser baerii♀ × A. schrenckii♂) induced by Aeromonas hydrophila infection - Ruiran Li; Xiaoni Wang; Denghang Yu; Qianrong Liang; Fuguo Liu; Lin Zhang; Bing Hu; Jin Wei; Lihe Liu; Jun Liu; Hongsen Xu (Animal Feed Science and Technology, 2023)

Application of Deep Learning-Based Object Detection Techniques in Fish Aquaculture: A Review - Hanchi Liu; Xin Ma; Yining Yu; Liang Wang; Lin Hao (Journal of Marine Science and Engineering, 2023)
Automated monitoring and analysis of fish’s growth status and behaviors can help scientific aquaculture management and reduce severe losses due to diseases or overfeeding. With developments in machine vision and deep learning (DL) techniques, DL-based object detection techniques have been extensively applied in aquaculture with the advantage of simultaneously classifying and localizing fish of interest in images. This study reviews the relevant research status of DL-based object detection techniques in fish counting, body length measurement, and individual behavior analysis in aquaculture. The research status is summarized from two aspects: image and video analysis. Moreover, the relevant technical details of DL-based object detection techniques applied to aquaculture are also summarized, including the dataset, image preprocessing methods, typical DL-based object detection algorithms, and evaluation metrics. Finally, the challenges and potential trends of DL-based object detection techniques in aquaculture are concluded and discussed. The review shows that generic DL-based object detection architectures have played important roles in aquaculture.

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Extended chloramination significantly enriched intracellular antibiotic resistance genes in drinking water treatment plants - Haibei Li; Hongling Yu; Yongbing Liang; Xudong Zhang; Dong Yang; Lin Wang; Danyang Shi; Tianjiao Chen; Shuqing Zhou; Jing Yin; Zhongwei Yang; Junwen Li; et al. (Water Research, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Evaluation of imide substance from Streptomyces atratus PY-1 for the biocontrol of Phytophthora blight - Chaoqun Zang; Tingting Kong; Bingbing Liang; Xiaozhou Liu; Jinhui Xie; Ying Lin; Xue Pei; Shuyi Yu; Chunhao Liang (European Journal of Plant Pathology, 2023)

The law of strength damage and deterioration of jointed sandstone after dry-wet cycles - Gui-lin Wang; Tian-yu Zhang; Liang Zhang (Journal of Mountain Science, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials - Zhe Zhao; Shumin Lin; Zhendong Yu; Ming Su; Bolong Liang; Shu-Xuan Liang; Xue-Hai Ju (Chemosphere, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Gut as the target tissue of mercury and the extraintestinal effects - Xue Tian; Xiaoying Lin; Jiating Zhao; Liwei Cui; Yuxi Gao; Yong-Liang Yu; Bai Li; Yu-Feng Li (Toxicology, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

How swimming style and schooling affect the hydrodynamics of two accelerating wavy hydrofoils - Zhonglu Lin; Amneet Pal Singh Bhalla; Boyce E. Griffith; Zi Sheng; Hongquan Li; Dongfang Liang; Yu Zhang (Ocean Engineering, 2023)

Evaluation of small-sized mounds formation mechanisms in China's Zhurong landing region - Yu Lin (林雨); Jiannan Zhao (赵健楠); Le Wang (王乐); Jun Huang (黄俊); Liang Zhang (张良); Long Xiao (肖龙) (Icarus, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults - Zhennan Lin; Shufeng Chen; Fangchao Liu; Jianxin Li; Jie Cao; Keyong Huang; Fengchao Liang; Jichun Chen; Hongfan Li; Jianfeng Huang; Dongsheng Hu; Chong Shen; et al. (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway - Sheau-Chung Tang; Chun-Te Lu; Jiunn-Liang Ko; Cheng-Hui Lin; Yu-Ping Hsiao (Chemico-Biological Interactions, 2023)

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Behavioral and transcriptomic changes in butenolide treated larvae of the cosmopolitan fouling bryozoan Bugulina (Bugula) neritina - Jin-You Liang; Yi-Fan Cheng; Xiao-Lin Huang; Ying Xu; Yue Him Wong; Yu Zhang (Frontiers in Marine Science, 2022)
The arborescent bryozoan Bugulina neritina is a cosmopolitan fouling species in sub-tropical to sub-temperate waters. The butenolide compound 5-octylfuran-2(5H)-one (hereafter named butenolide) reportedly inhibits larval settlement of B. neritina , but its effect on the larval behavioral and transcriptomic responses remained unclear. We report that 10 μg mL -1 or higher concentration of butenolide and/or prolonged treatment (10 h or longer) resulted in significant increase in larval mortality and prominent spiral larval swimming behavior. The transcriptomic analyses not only revealed up-regulation of typical stress-related protein genes in response to 10 mg mL -1 butenolide treatment, but also indicated up-regulation of mucin , synaptic genes and nitric oxide signaling genes. In addition, the expression of developmental genes and lipid biosynthesis genes were also affected. Overall, our larval behavior and transcriptome analyses reflected the impact of butenolide on the metabolism, neuronal and molecular signaling in B. neritina larvae.

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Effects of cervicothoracic postures on the stiffness of trapezius muscles - Hongying Liang; Suiqing Yu; Man Hao; Weixin Deng; Ming Lin; Zheng Zhang; Chunlong Liu (Medical & Biological Engineering & Computing, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Construction of an egg-like DTAB/SiO2 composite for the enhanced removal of uranium - Tuckyun Cheang; Hongyan Zhou; Weihao Lin; JiaJun Zheng; Liang Yu; Yongcheng Zhang (Environmental Science and Pollution Research, 2022)

Natural variation of the BRD2 allele affects plant height and grain size in rice - Jinpeng Huang; Zhiming Chen; Jiajia Lin; Jinwen Chen; Menghao Wei; Liang Liu; Feng Yu; Zesen Zhang; Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Tiansheng Wang; et al. (Planta, 2022)

Deep learning based diagnosis of Parkinson’s Disease using diffusion magnetic resonance imaging - Hengling Zhao; Chih-Chien Tsai; Mingyi Zhou; Yipeng Liu; Yao-Liang Chen; Fan Huang; Yu-Chun Lin; Jiun-Jie Wang (Brain Imaging and Behavior, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Characterization of Water Transport in Porous Building Materials Based on an Analytical Spontaneous Imbibition Model - Ming-Liang Qu; Sheng-Yue Lu; Qingyang Lin; Sajjad Foroughi; Zi-Tao Yu; Martin J. Blunt (Transport in Porous Media, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Elastic-energy imaging condition based on energy-flow vector - Xiao-Yu Zhang; Yi Zheng; Chuan-Lin He; Zhan-Yuan Liang (Applied Geophysics, 2022)

Epidemiological characteristics of gonorrhea and its influential meteorological factors: a 14-year retrospective assessment in China - Jin Bu; Liang-Jia Zhou; Xiang Xiao; Qian Yue; Gang Hu; Pei Jiang; Jing Chen; Yu Lin (Environmental Science and Pollution Research, 2022)

Comparative study on fecal flora and blood biochemical indexes in normal and diarrhea British Shorthair cats - Yuan-Yuan Yu; Lin Liang; Hong-Bo Xiao (Archives of Microbiology, 2022)

Short-term variations and influencing factors of suspended sediment concentrations at the Heisha Beach, Guangdong, China - Jintang Ou; Haoyan Dong; Liangwen Jia; Xiangxin Luo; Zixiao He; Kanglin Chen; Jing Liu; Yitong Lin; Mingdong Yu; Mingen Liang (Acta Oceanologica Sinica, 2022)

Contraction and warming of Antarctic Bottom Water in the Amundsen Sea - Yu Bai; Liang Zhao; Jingen Xiao; Shiying Lin (Acta Oceanologica Sinica, 2022)

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Ag3PO4-based photocatalysts and their application in organic-polluted wastewater treatment - Chunmu Yu; Xiaojuan Chen; Ning Li; Yue Zhang; Sailin Li; Jieming Chen; Liang Yao; Kaichun Lin; Yiqi Lai; Xinru Deng (Environmental Science and Pollution Research, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Characterization of alkaloids in radix Sophora tonkinensis by UPLC-Q-TOF-MS/MS and its application in the comparison of two different habitats - Xing-Xing Zong; Yu Wang; Jia-Liang Xiong; Yu-Hui Ping; Qiong-Lin Liang (Natural Product Research, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Novel wing display and divergent agonistic behaviors of two incipient Psolodesmus damselflies - Leocris S. Batucan; Yu-Hsun Hsu; Jak W. Maliszewski; Liang-Jong Wang; Chung-Ping Lin (The Science of Nature, 2021)

Serum Neurofilament Light: a Potential Diagnostic and Prognostic Biomarker in Obstetric Posterior Reversible Encephalopathy Syndrome - Xiaobo Fang; Yanling Liang; Weixi Zhang; Qiong Wang; Jingsi Chen; Jia Chen; Yongqiang Lin; Yanli Chen; Li Yu; Haibin Wang; Dunjin Chen (Molecular Neurobiology, 2021)

Wave-ice dynamical interaction: a numerical model and its application - Yang Zhang; Changsheng Chen; Guoping Gao; Jianhua Qi; Huichan Lin; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2021)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Effect of Quicklime on Microbial Community in Strong Acidic Soil - Junwei Liang; Xiangquan Yu; Yafan Cao; Jiguang Zhang; Ning Yan; Lin Xue; Xianjie Cai; Guoming Shen (Journal of Soil Science and Plant Nutrition, 2021)

Effects of periodically varying codes on separation of multisource blended data - Meng-Yao Jiao; Tian-Yue Hu; Yang Liu; Zhen-Zhen Yu; Shang-Lin Liang; Li-Chao Liu; Ji-Wei (Applied Geophysics, 2021)

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Environmental microorganism classification using optimized deep learning model - Chih-Ming Liang; Chun-Chi Lai; Szu-Hong Wang; Yu-Hao Lin (Environmental Science and Pollution Research, 2021)

Influence of different fluidization and gasification parameters on syngas composition and heavy metal retention in a two-stage fluidized bed gasification process - Jia-Hong Kuo; Chiou-Liang Lin; Chang-Yu Ho; Jia-Chi Hung (Environmental Science and Pollution Research, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Two new species of Hortiboletus (Boletaceae, Boletales) from China - Hui-Jing Xie; Wen-Fei Lin; Shuai Jiang; Rou Xue; Lu-Ling Wu; Yu-Zhuo Zhang; Zhi-Qun Liang; Nian-Kai Zeng; Ming-Sheng Su (Mycological Progress, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Strength attenuation effects on rate-dependent law of stress development of frozen sand - Xiao-Liang Yao; Ji-Lin Qi; Ming-Yi Zhang; Fan Yu (European Journal of Environmental and Civil Engineering, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

lncRNA-XIST protects the hypoxia-induced cardiomyocyte injury through regulating the miR-125b-hexokianse 2 axis - Ji-Lin Fan; Ting-Ting Zhu; Zhen-Yu Xue; Wen-Qing Ren; Jing-Qi Guo; Heng-Yi Zhao; Shi-Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Swelling characteristics of andesite foundation induced by water immersion and their influence on ballastless track subgrade - Jun-yi Duan; Guo-lin Yang; Min Hu; Xiao-qin Lei; Yu-liang Lin (Journal of Mountain Science, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Effects of Short Term Methylmercury Exposure on Growth and Development of the Large Yellow Croaker Embryos and Larvae - Xiang Yu; Fangzhu Wu; Xiaoqun Xu; Quanzhen Chen; Lin Huang; Berhane Teklehaimanot Tesfai; Liang Cao; Xudan Xu; Shuozeng Dou; Wei Huang (Frontiers in Marine Science, 2019)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Transcriptome analysis in different chieh-qua cultivars provides new insights into drought-stress response - Min Wang; Xiaoming He; Biao Jiang; Wenrui Liu; Yu’e Lin; Dasen Xie; Zhaojun Liang; Lihui Chen; Qingwu Peng (Plant Biotechnology Reports, 2019)

Integrated analysis of hypoxia-induced miR-210 signature as a potential prognostic biomarker of hepatocellular carcinoma: a study based on The Cancer Genome Atlas - Yi Dai; Ji-liang Shen; Xue-yong Zheng; Tian-yu Lin; Hai-tao Yu (Journal of Zhejiang University-SCIENCE B, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Crystal structure of norsethite-type BaMn(CO3)2 and its pressure-induced transition investigated by Raman spectroscopy - Wen Liang; Lin Li; Yuan Yin; Rui Li; Zeming Li; Xiqiang Liu; Chaoshuai Zhao; Shuguang Yang; Yong Meng; Zengsheng Li; Yu He; Heping Li (Physics and Chemistry of Minerals, 2019)

Big‐sized trees overrule remaining trees' attributes and species richness as determinants of aboveground biomass in tropical forests - Arshad Ali; Si‐Liang Lin; Jie‐Kun He; Fan‐Mao Kong; Jie‐Hua Yu; Hai‐Sheng Jiang (Global Change Biology, 2019)
Large‐diameter, tall‐stature, and big‐crown trees are the main stand structures of forests, generally contributing a large fraction of aboveground biomass, and hence play an important role in climate change mitigation strategies. Here, we hypothesized that the effects of large‐diameter, tall‐stature, and big‐crown trees overrule the effects of species richness and remaining trees attributes on aboveground biomass in tropical forests (i.e., we term the “big‐sized trees hypothesis”). Specifically, we assessed the importance of: (a) the “top 1% big‐sized trees effect” relative to species richness; (b) the “99% remaining trees effect” relative to species richness; and (c) the “top 1% big‐sized trees effect” relative to the “99% remaining trees effect” and species richness on aboveground biomass. Using environmental factor and forest inventory datasets from 712 tropical forest plots in Hainan Island of southern China, we tested several structural equation models for disentangling the relative effects of big‐sized trees, remaining trees attributes, and species richness on aboveground biomass, while considering for the full (indirect effects only) and partial (direct and indirect effects) mediation effects of climatic and soil conditions, as well as interactions between species richness and trees attributes. We found that top 1% big‐sized trees attributes strongly increased aboveground biomass (i.e., explained 55%–70% of the accounted variation) compared to species richness (2%–18%) and 99% remaining trees attributes (6%–10%). In addition, species richness increased aboveground biomass indirectly via increasing big‐sized trees but via decreasing remaining trees. Hence, we show that the “big‐sized trees effect” overrides the effects of remaining trees attributes and species richness on aboveground biomass in tropical forests. This study also indicates that big‐sized trees may be more susceptible to atmospheric drought. We argue that the effects of big‐sized trees on species richness and aboveground biomass should be tested for better understanding of the ecological mechanisms underlying forest functioning.

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

A special issue to mark the 90th Anniversary of College of Life Sciences, Zhejiang University - Jin-rong Peng; Kun-liang Guan; De-yuan Hong; Xin-hua Lin; Huan-ming Yang; Yu-xian Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Are glutamate transporters neuroprotective or neurodegenerative during cerebral ischemia? - Li-Nan Zhang; Liang Hao; Yu-Song Guo; Hai-Yan Wang; Lin-lin Li; Li-Zhe Liu; Wen-Bin Li (Journal of Molecular Medicine, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

Herpes zoster and the risks of osteoporosis and fracture: a nationwide cohort study - Shu-Man Lin; Chih-Yung Wang; Ying-Yu Chen; Jen-Hung Wang; Chung-Chao Liang; Huei-Kai Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Inhibition of macrophage inflammatory protein-1β improves endothelial progenitor cell function and ischemia-induced angiogenesis in diabetes - Ting-Ting Chang; Liang-Yu Lin; Jaw-Wen Chen (Angiogenesis, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

Single crystal growth, crystalline structure investigation and high-pressure behavior of impurity-free siderite (FeCO3) - Wen Liang; Yuan Yin; Zeming Li; Rui Li; Lin Li; Yu He; Haini Dong; Zengsheng Li; Shuai Yan; Shuangmeng Zhai; Heping Li (Physics and Chemistry of Minerals, 2018)

Genetic analysis and QTL mapping of fruit-related traits in wax gourd (Benincasa hispida) - Wenrui Liu; Biao Jiang; Qingwu Peng; Xiaoming He; Yu’e Lin; Min Wang; Zhaojun Liang; Dasen Xie; Kailin Hu (Euphytica, 2018)

Localization of Maize Critical N Curve and Estimation of NNI by Chlorophyll - Xiao-Gui Liang; Zuo-Lin Zhang; Li-Li Zhou; Si Shen; Zhen Gao; Li Zhang; Shan Lin; Yu-Qiang Pan; Shun-Li Zhou (International Journal of Plant Production, 2018)

Single crystal growth, characterization and high-pressure Raman spectroscopy of impurity-free magnesite (MgCO3) - Wen Liang; Zeming Li; Yuan Yin; Rui Li; Lin Chen; Yu He; Haini Dong; Lidong Dai; Heping Li (Physics and Chemistry of Minerals, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Microphytoplankton community structure in the western Arctic Ocean: surface layer variability of geographic and temporal considerations in summer - Yu Wang; Peng Xiang; Jian-hua Kang; You-yin Ye; Geng-ming Lin; Qing-liang Yang; Mao Lin (Hydrobiologia, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Analysis of fecal microbiota in patients with functional constipation undergoing treatment with synbiotics - Lin Sheng Huang; Cheng Kong; Ren Yuan Gao; Xuebing Yan; Hong Jing Yu; Bin Wen; Qi Zhu; Tong Yi Shen; Zhen Liang Sun; Huan Long Qin (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Characterization of the complete chloroplast genome of the Chinese cherry Prunus pseudocerasus (Rosaceae) - Ying Feng; Tao Liu; Xiao-Yu Wang; Bin-Bin Li; Cheng-Lin Liang; Yu-Liang Cai (Conservation Genetics Resources, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

Size structure of biomass and primary production of phytoplankton: environmental impact analysis in the Dongsha natural gas hydrate zone, northern South China Sea - Jianhua Kang; Qianyong Liang; Jianjun Wang; Yili Lin; Xuebao He; Zhen Xia; Xinqing Zheng; Yu Wang (Acta Oceanologica Sinica, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Secretion of Down Syndrome Critical Region 1 Isoform 4 in Ischemic Retinal Ganglion Cells Displays Anti-Angiogenic Properties Via NFATc1-Dependent Pathway - Yue Xu; Boyu Yang; Yaguang Hu; Lin Lu; Xi Lu; Jiawei Wang; Qinmeng Shu; Qiaochu Cheng; Shanshan Yu; Fan Xu; Jingjing Huang; Xiaoling Liang (Molecular Neurobiology, 2017)

Different effects of neuropeptide Y on proliferation of vascular smooth muscle cells via regulation of Geminin - Zhou-qin Jiang; You-li Zhou; Xia Chen; Lin-yu Li; Shi-yu Liang; Shu Lin; Mao-qin Shu (Molecular and Cellular Biochemistry, 2017)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

Identification and expression patterns of 20-hydroxyecdysone-responsive genes from Procambarus clarkii - Bao-Jian Zhu; Lin Tang; Ying-Ying Yu; Dao-Jun Wang; Chao-Liang Liu (Genes & Genomics, 2017)

The complete mitogenome of sea slug, Nembrotha kubaryana (Mollusca: Polyceridae) - Peng Xiang; Mao Lin; Yu Wang; Gilbert Audira; Sung-Tzu Liang; Chung-Der Hsiao (Conservation Genetics Resources, 2017)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

A sensitive duplex nanoparticle-assisted PCR assay for identifying porcine epidemic diarrhea virus and porcine transmissible gastroenteritis virus from clinical specimens - Yu Zhu; Lin Liang; Yakun Luo; Guihua Wang; Chunren Wang; Yudong Cui; Xia Ai; Shangjin Cui (Virus Genes, 2017)

Characterisation of siRNAs derived from new isolates of bamboo mosaic virus and their associated satellites in infected ma bamboo (Dendrocalamus latiflorus) - Wenwu Lin; Wenkai Yan; Wenting Yang; Chaowei Yu; Huihuang Chen; Wen Zhang; Zujian Wu; Liang Yang; Lianhui Xie (Archives of Virology, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Multi-resolution graph-based clustering analysis for lithofacies identification from well log data: Case study of intraplatform bank gas fields, Amu Darya Basin - Yu Tian; Hong Xu; Xing-Yang Zhang; Hong-Jun Wang; Tong-Cui Guo; Liang-Jie Zhang; Xing-Lin Gong (Applied Geophysics, 2016)

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Reliability back analysis of shear strength parameters of landslide with three-dimensional upper bound limit analysis theory - Lian-Heng Zhao; Shi Zuo; Yu-Liang Lin; Liang Li; Yingbin Zhang (Landslides, 2016)

A new tigliane-type diterpene from Euphorbia dracunculoides Lam - Lin-Feng Dai; Qian Liang; Tie Liu; Ming-Yu He; Ping Zhao; Wen-Hui Xu (Natural Product Research, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Paleoclimatic record from Chumbur-Kosa section in Sea of Azov region since Marine Isotope Stage 11 - Ye Liang; Tai-bao Yang; Andrey Aleksevitch Velichko; Biao Zeng; Pei-hong Shi; Lin-dong Wang; Yi He; Jie Chen; Yu Chen (Journal of Mountain Science, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Anti-angiogenic and anti-inflammatory effect of Magnolol in the oxygen-induced retinopathy model - Boyu Yang; Yue Xu; Shanshan Yu; Yongsheng Huang; Lin Lu; Xiaoling Liang (Inflammation Research, 2016)

Erratum to: The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Effects of simulated acid rain on microbial characteristics in a lateritic red soil - Hua-qin Xu; Jia-en Zhang; Ying Ouyang; Ling Lin; Guo-ming Quan; Ben-liang Zhao; Jia-yu Yu (Environmental Science and Pollution Research, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Selenium geochemical distribution in the environment and predicted human daily dietary intake in northeastern Qinghai, China - Dasong Yu; Dongli Liang; Lingming Lei; Rong Zhang; Xiaofeng Sun; Zhiqing Lin (Environmental Science and Pollution Research, 2015)

Diacylglycerol Kinase (DGK) Inhibitor II (R59949) Could Suppress Retinal Neovascularization and Protect Retinal Astrocytes in an Oxygen-Induced Retinopathy Model - Lu Yang; Yue Xu; Weihua Li; Boyu Yang; Shanshan Yu; Huanjiao Zhou; Cheng Yang; Fan Xu; Jun Wang; Yi Gao; Yongsheng Huang; Lin Lu; et al. (Journal of Molecular Neuroscience, 2015)

Assessing the authenticity of commercial deep-sea drinking water by chemical and isotopic approaches - Tsung-Ren Peng; Wen-Jui Liang; Tsang-Sen Liu; Yu-Wen Lin; Wen-Jun Zhan (Isotopes in Environmental and Health Studies, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Seismic response of embankment slopes with different reinforcing measures in shaking table tests - Yu-liang Lin; Wu-ming Leng; Guo-lin Yang; Liang Li; Jun-Sheng Yang (Natural Hazards, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Dissection of qTGW1.2 to three QTLs for grain weight and grain size in rice (Oryza sativa L.) - Lin-Lin Wang; Yu-Yu Chen; Liang Guo; Hong-Wei Zhang; Ye-Yang Fan; Jie-Yun Zhuang (Euphytica, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

Observation of the middle intestinal tight junction structure, cloning and studying tissue distribution of the four Claudin genes of the grass carp (Ctenopharyngodon idellus) - Fan Xu; Yuan-Tu Ye; Chun-Fang Cai; Ping Wu; Lin Song; Meng Liu; Lin-Jie Yao; Jiao-Jiao Dong; Yu-Wei Huang; Zhi Gong; Jie Qin; Liang Song (Fish Physiology and Biochemistry, 2014)

Global and local brain network reorganization in attention-deficit/hyperactivity disorder - Pan Lin; Jubao Sun; Gang Yu; Ying Wu; Yong Yang; Meilin Liang; Xin Liu (Brain Imaging and Behavior, 2014)

QTLs for uppermost internode and spike length in two wheat RIL populations and their affect upon plant height at an individual QTL level - Ma Yu; Shuang-Lin Mao; Guo-Yue Chen; Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Euphytica, 2014)

Suppression of PI3K/Akt signaling by synthetic bichalcone analog TSWU-CD4 induces ER stress- and Bax/Bak-mediated apoptosis of cancer cells - Meng-Liang Lin; Shih-Shun Chen; Ren-Yu Huang; Yao-Cheng Lu; Yu-Ren Liao; Mopuru Vijaya Bhaskar Reddy; Chuan-Chun Lee; Tian-Shung Wu (Apoptosis, 2014)

Contrasting elevational diversity patterns between eukaryotic soil microbes and plants - Congcong Shen; Wenju Liang; Yu Shi; Xiangui Lin; Huayong Zhang; Xian Wu; Gary Xie; Patrick Chain; Paul Grogan; Haiyan Chu (Ecology, 2014)
The diversity of eukaryotic macroorganisms such as animals and plants usually declines with increasing elevation and latitude. By contrast, the community structure of prokaryotes such as soil bacteria does not generally correlate with elevation or latitude, suggesting that differences in fundamental cell biology and/or body size strongly influence diversity patterns. To distinguish the influences of these two factors, soil eukaryotic microorganism community structure was investigated in six representative vegetation sites along an elevational gradient from forest to alpine tundra on Changbai Mountain in Northeast China, and compared with our previous determination of soil bacterial community structure along the same gradient. Using bar‐coded pyrosequencing, we found strong site differences in eukaryotic microbial community composition. However, diversity of the total eukaryotic microorganism community (or just the fungi or protists alone) did not correlate with elevation. Instead, the patterns of diversity and composition in the total eukaryotic microbial community (and in the protist community alone) were closely correlated with soil pH, suggesting that just as for bacteria, acidity is a particularly important determinant of eukaryotic microbial distributions. By contrast, as expected, plant diversity at the same sites declined along our elevational gradient. These results together suggest that elevational diversity patterns exhibited by eukaryotic microorganisms are fundamentally different from those of plants.

A new antioxidant flavone glycoside from Scutellaria baicalensis Georgi - Meng-Hua Wang; Lin-Zhen Li; Jian-Bo Sun; Fei-Hua Wu; Jing-Yu Liang (Natural Product Research, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

GSK3β Promotes the Differentiation of Oligodendrocyte Precursor Cells via β-Catenin-Mediated Transcriptional Regulation - Liang Zhou; Chong-Yu Shao; Si-min Xu; Jiao Ma; Ya-Jun Xie; Lin Zhou; Peng Teng; Yin Wang; Mengsheng Qiu; Ying Shen (Molecular Neurobiology, 2014)

Flavonoids and other constituents from Aletris spicata and their chemotaxonomic significance - Lin-Zhen Li; Meng-Hua Wang; Jian-Bo Sun; Jing-Yu Liang (Natural Product Research, 2014)

Cannabinoid receptor 1 disturbance of PPARγ2 augments hyperglycemia induction of mesangial inflammation and fibrosis in renal glomeruli - Chun-Liang Lin; Yung-Chien Hsu; Pei-Hsien Lee; Chen-Chou Lei; Jeng-Yi Wang; Yu-Ting Huang; Shao-Yu Wang; Feng-Sheng Wang (Journal of Molecular Medicine, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Variants of COL3A1 Are Associated with the Risk of Stroke Recurrence and Prognosis in the Chinese Population: a Prospective Study - Wenfei Lv; Yahui Lin; Weihua Song; Kai Sun; Hui Yu; Yinhui Zhang; Channa Zhang; Liang Li; Miaomiao Suo; Rutai Hui; Jingzhou Chen (Journal of Molecular Neuroscience, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Identification of Key Licorice Constituents Which Interact with Cytochrome P450: Evaluation by LC/MS/MS Cocktail Assay and Metabolic Profiling - Xue Qiao; Shuai Ji; Si-wang Yu; Xiong-hao Lin; Hong-wei Jin; Yao-kai Duan; Liang-ren Zhang; De-an Guo; Min Ye (The AAPS Journal, 2014)

Analysis of synonymous codon usage patterns in the genus Rhizobium - Xinxin Wang; Liang Wu; Ping Zhou; Shengfeng Zhu; Wei An; Yu Chen; Lin Zhao (World Journal of Microbiology and Biotechnology, 2013)

Dynamic behavior of railway embankment slope subjected to seismic excitation - Yu-liang Lin; Guo-lin Yang (Natural Hazards, 2013)

Effects of rainfall and manure application on phosphorus leaching in field lysimeters during fallow season - Qiao Yun Xue; Pei Bin Dai; Da Sheng Sun; Cheng Liang Sun; Ling Yu Qi; Anne Ostermann; Yao He; Xian Yong Lin (Journal of Soils and Sediments, 2013)

First report on the allelopathic effect of Tychonema bourrellyi (Cyanobacteria) against Microcystis aeruginosa (Cyanobacteria) - Jihai Shao; Liang Peng; Si Luo; Gongliang Yu; Ji-dong Gu; Shen Lin; Renhui Li (Journal of Applied Phycology, 2013)

Transgenic expression of an insect diapause-specific peptide (DSP) in Arabidopsis resists phytopathogenic fungal attacks - Tingquan Wu; Yongfang Chen; Weida Chen; Shenghao Zou; Yongqing Zhang; Yu’e Lin; Zhaojun Liang; Dingzhong Tang (European Journal of Plant Pathology, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

TGFβ1 Treatment Reduces Hippocampal Damage, Spontaneous Recurrent Seizures, and Learning Memory Deficits in Pilocarpine-Treated Rats - Liang-Yong Li; Jia-Lin Li; Hui-Min Zhang; Wen-Ming Yang; Kai Wang; Yuan Fang; Yu Wang (Journal of Molecular Neuroscience, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum - Xia-zhen Yu; Tao Ji; Xue-li Bai; Liang Liang; Lin-yan Wang; Wei Chen; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Erratum to: Single nucleotide polymorphisms in the human corticosteroid-binding globulin promoter alter transcriptional activity - Yue Li; Liang Wu; JingHui Lei; Cheng Zhu; HongMei Wang; XiaoGuang Yu; HaiYan Lin (Science China Life Sciences, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Single nucleotide polymorphisms in the human corticosteroid-binding globulin promoter alter transcriptional activity - Yue Li; Liang Wu; JingHui Lei; Cheng Zhu; HongMei Wang; XiaoGuang Yu; HaiYan Lin (Science China Life Sciences, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Alleviative effect of quercetin on germ cells intoxicated by 3-methyl-4-nitrophenol from diesel exhaust particles - Tong-liang Bu; Yu-dong Jia; Jin-xing Lin; Yu-ling Mi; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

The combined influence of background climate and urbanization on the regional warming in Southeast China - Peng Si; Yu Ren; Dongpo Liang; Bingwen Lin (Journal of Geographical Sciences, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Genomic sequencing and analysis of Chilli ringspot virus, a novel potyvirus - Dian Gong; Jian-Hua Wang; Zhan-Song Lin; Shao-Yan Zhang; Yu-Liang Zhang; Nai-Tong Yu; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2011)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Detection of porcine circovirus type 1 in commercial porcine vaccines by loop-mediated isothermal amplification - Chun Wang; Victor Fei Pang; Chian-Ren Jeng; Fan Lee; Yu-Wen Huang; Yeou-Liang Lin; Shih-Hsuan Hsiao; Shiow-Suey Lai (Folia Microbiologica, 2011)

Factors affecting lipid accumulation by Nannochloropsis oculata in a two-stage cultivation process - Chia-Hung Su; Liang-Jung Chien; James Gomes; Yu-Sheng Lin; Yuan-Kun Yu; Jhang-Song Liou; Rong-Jhih Syu (Journal of Applied Phycology, 2011)

On the forced tangentially-averaged radial-vertical circulation within vortices. Part II: The transformation of Tropical Storm Haima (2004) - Yu-Kun Qian; Chang-Xia Liang; Qiaoqian Liang; Liangxun Lin; Zhuojian Yuan (Advances in Atmospheric Sciences, 2011)

Diversity of killer cell immunoglobulin-like receptor genes in four ethnic groups in China - Yufeng Yao; Lei Shi; Yufen Tao; Keqin Lin; Shuyuan Liu; Liang Yu; Zhaoqing Yang; Wen Yi; Xiaoqin Huang; Hao Sun; Jiayou Chu; Li Shi (Immunogenetics, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

Phytoplankton variation and its relationship with the environment in Xiangxi Bay in spring after damming of the Three-Gorges, China - Guangjie Zhou; Xuemin Zhao; Yonghong Bi; Yubin Liang; Jianlin Hu; Min Yang; Yu Mei; Kongxian Zhu; Lin Zhang; Zhengyu Hu (Environmental Monitoring and Assessment, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Characterization and expression of chicken selenoprotein W - Bor-Rung Ou; Mei-Jung Jiang; Chao-Hsiang Lin; Yu-Chuan Liang; Kuei-Jen Lee; Jan-Ying Yeh (BioMetals, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Neural correlates of audio-visual modal interference inhibition investigated in children by ERP - YiWen Wang; ChongDe Lin; Jing Liang; Yu Wang; WenXin Zhang (Science China Life Sciences, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Artificial gynogenesis and assessment of homozygosity in meiotic gynogens of spotted halibut (Verasper variegatus) - Xiang-Shan Ji; Song-Lin Chen; Jing-Feng Yang; Hong-Yu Ma; Yun-Liang Jiang (Aquaculture International, 2010)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Berberine suppresses intestinal disaccharidases with beneficial metabolic effects in diabetic states, evidences from in vivo and in vitro study - Li Liu; Yun-Li Yu; Jian-Song Yang; Yang Li; Yao-Wu Liu; Yan Liang; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Effects of dietary medicinal herbs and Bacillus on survival, growth, body composition, and digestive enzyme activity of the white shrimp Litopenaeus vannamei - Ming-Chao Yu; Zhuo-Jia Li; Hei-Zhao Lin; Guo-Liang Wen; Shen Ma (Aquaculture International, 2009)

Deletion analysis of the C-terminal region of a molecular chaperone DnaK from Bacillus licheniformis - Wan-Chi Liang; Min-Guan Lin; Meng-Chun Chi; Hui-Yu Hu; Huei-Fen Lo; Hui-Ping Chang; Long-Liu Lin (Archives of Microbiology, 2009)

Inhibition of NFkappaB by activated c-Jun NH2 terminal kinase 1 acts as a switch for C2C12 cell death under excessive stretch - Jiali Tan; Wei Kuang; Zuolin Jin; Fang Jin; Lin Xu; Qiujun Yu; Liang Kong; Guang Zeng; Xiao Yuan; Yinzhong Duan (Apoptosis, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Effects of dietary Bacillus and medicinal herbs on the growth, digestive enzyme activity, and serum biochemical parameters of the shrimp Litopenaeus vannamei - Ming-Chao Yu; Zhuo-Jia Li; Hei-Zhao Lin; Guo-Liang Wen; Shen Ma (Aquaculture International, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Attenuation by methyl mercury and mercuric sulfide of pentobarbital induced hypnotic tolerance in mice through inhibition of ATPase activities and nitric oxide production in cerebral cortex - Jiunn-Jye Chuu; Zih-Ning Huang; Hsun-Hsin Yu; Liang-Hao Chang; Shoei-Yn Lin-Shiau (Archives of Toxicology, 2008)

Characteristics of Atmospheric Aerosol and Acidic Gases from Urban and Forest Sites in Central Taiwan - Man-Ting Cheng; Chuen-Liang Horng; Yu-Chi Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Activation of Helicobacter pylori inorganic pyrophosphatase and the importance of Cys16 in thermostability, enzyme activation and quaternary structure - Mon-Juan Lee; Haimei Huang; Wei Lin; Ray-Rong Yang; Chien-Liang Liu; Chung-Yu Huang (Archives of Microbiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Expression of truncated phosphoproteins of Nipah virus and Hendra virus in Escherichia coli for the differentiation of henipavirus infections - Ji-Ming Chen; Koon Chu Yaiw; Meng Yu; Lin-Fa Wang; Qing-Hua Wang; Gary Crameri; Zhi-Liang Wang (Biotechnology Letters, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Annual Variations of Gonadotropin Content and Ovarian Development of Feral Female Catfish, Silurus asotus, in Central China - Hai Sh Wen; Hao R. Lin; Yu Z. Mao; Liang Wang; Ya P. Zhang (Environmental Biology of Fishes, 2003)

Biotic communities of freshwater marshes and mangroves in relation to saltwater incursions: implications for wetland regulation - Hsing-Juh Lin; Kwang-Tsao Shao; Wen-Liang Chiou; Can-Jen W Maa; Hwey-Lian Hsieh; Wen-Lung Wu; Lucia L. Severinghaus; Yu-Tzu Wang (Biodiversity and Conservation, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)